KETERDIFERENSIALAN FUNGSI LIPSCHITZ DI DALAM RUANG BERNORMA - , Dwi Nur Yunianti ([Yogyakarta] : Universitas Gadjah Mada, 2012)
In this thesis, we discuss about the connection between Lipschitz function and differentiable functions on normed spaces. First, we investigate the connection between Frechet differentiable functions and Gateaux differentiable functions. Next, we investigate the connection between Lipschitz functions and FrÃ©chet differentiable functions, and the connection between Lipschitz functions and Gateaux differentiable functions by properties of the Radon Nikodym (Radon Nikodym Property or RNP).